Accuracy of a flapless protocol for computer‐guided zygomatic implant placement in human cadavers: expectations and reality. Issue 1 (27th January 2015) - Schiroli, Guido; Angiero, Francesca; Zangerl, Antoniettel; Benedicenti, Stefano; Ferrante, Franco; Widmann, Gerlig
Abstract: Background: This work evaluated the accuracy and safety of a protocol for minimally‐invasive flapless zygomatic implant placement that uses computer‐guided stereolithographic mucosa‐supported surgical templates. Methods: A total of six zygomatic implants were placed in three formalin‐fixed human cadaver heads, with edentulous and severely atrophic posterior maxillae. CT scans of each cadaver head were performed after zygomatic implant placement, to evaluate the lateral error (LE) at implant tip and base, and the angular error (AE) of the implant body. Results: Excluding the implant placed outside the drilling channel, the LE at the implant base was less than 1 mm in all cases. The average LE at the tip was 3.86 mm, and the AE was less than 6° in all cases, with an average of 4.5°. Conclusion: Computer‐guided minimally‐invasive flapless zygomatic implant surgery remains challenging. Careful planning and perfect stability of the surgical guide are essential. Copyright © 2015 John Wiley & Sons, Ltd.